Natural killer cells affect the natural course, drug resistance, and prognosis of multiple myeloma - Zhang, Li; Peng, Xiaohuan; Ma, Tao; Liu, Jia; Yi, Zhigang; Bai, Jun; Li, Yanhong; Li, Lijuan; Zhang, Liansheng (Frontiers in Cell and Developmental Biology, 2024)
Multiple myeloma (MM), a stage-developed plasma cell malignancy, evolves from monoclonal gammopathy of undetermined significance (MGUS) or smoldering MM (SMM). Emerging therapies including immunomodulatory drugs, proteasome inhibitors, monoclonal antibodies, chimeric antigen-T/natural killer (NK) cells, bispecific T-cell engagers, selective inhibitors of nuclear export, and small-molecule targeted therapy have considerably improved patient survival. However, MM remains incurable owing to inevitable drug resistance and postrelapse rapid progression. NK cells with germline-encoded receptors are involved in the natural evolution of MGUS/SMM to active MM. NK cells actively recognize aberrant plasma cells undergoing malignant transformation but are yet to proliferate during the elimination phase, a process that has not been revealed in the immune editing theory. They are potential effector cells that have been neglected in the therapeutic process. Herein, we characterized changes in NK cells regarding disease evolution and elucidated its role in the early clinical monitoring of MM.